Impact of malnutrition on scholastic performance among school children in Mysuru - Amogha Shree; M.R. Narayana Murthy (Elsevier, 2021)
Background: The greatest national resources of any country are the Children and they are the one who build the future of the Nation. In developing countries malnutrition among children is the serious issue. Many researches indicate that health problems due to malnutrition in school - age children are the most common cause of absenteeism and unsatisfactory scholastic performance. With this context this study was conducted to assess the impact of malnutrition on scholastic performance among school children. Methodology: Cross sectional study was done among high school children. Information about student's age was collected from school records. Height and weight measurements were taken using standard methods and BMI was transformed into WHO 2007 Z scores. Children were clinically examined for pallor. Academic performance of the students was assessed by the grades scored in their 1st internals. Data was entered in Microsoft excel sheet and analyzed using SPSS software version 24. Results: Among 320 students, 51.6% were boys and 48.4% were girls, 80.3% of the students have scored more than 50%, out of them 14% have secured A+ grade. 37.5% were malnourished and among them 50% were thin. There is a statistically significant association between nutritional status and scholastic performance (p 0.04). Conclusions: The study shows a statistically significant association between nutritional status and scholastic performance which concludes that increase in the nutritional status of children in turn increases the academic achievement.